BS EN IEC 60601-2-2 AMD1. Medical electrical equipment. Part 2-2. Particular requirements for the basic safety and essential performance of high frequency surgical equipment and high frequency surgical accessories (21st May 2021) - British Standards Institution,
No abstract available